Base Erosion and Profit Shifting (BEPS): o combate ao treaty abuse mediante o fortalecimento das Cláusulas de Limitação de Benefícios (LOB) - Pegoraro, Andressa (2015)
This paper aims to analyze the BEPS Project that was developed by OECD as an action plan against base erosion and profit shifting in international transactions. The OECD is developing a global action plan based on in-depth analysis of the identified pressure areas with a view to provide suggestion for amending the tax law and concrete solutions to address aggressive tax planning. This paper addresses specifically the Action 6 of the BEPS Project, which seeks to prevent treaty abuses through LOB clause proposed by OECD. The OECD was influenced by the LOB clause included in the north-american model convention, which was also analyzed in this paper, with the intention of predicting the main difficulties that will be faced by the OECD Member States in its concrete application. Finally, it covers the LOB clauses included in certain double tax treaties entered by Brazil and the Action 6 impacts in Brazil’s currently and future double tax treaties